Zoonotic infections in pediatric patients with acute leukemia. Issue 12 (19th August 2013) - Lothstein, Katherine; Fisher, Brian; Li, Yimei; Seif, Alix; Harris, Tracey; Torp, Kari; Kavcic, Marko; Huang, Yuan‐Shung V.; Rheingold, Susan R.; Aplenc, Richard
Abstract Few studies have described the impact of zoonotic diseases in children with leukemia. This study aimed to describe the frequency of and associated demographic factors for zoonotic diseases in pediatric acute leukemia patients. Descriptive and comparative statistics relative to age, sex, and patient region were performed on an assembled 11‐year retrospective cohort of acute leukemia patients. Of 10, 197 patients, 88 patients (0.86%) were found to have a zoonotic infection. Gastrointestinal diseases were the most commonly (86.4%) identified zoonotic illnesses. Although rare, zoonotic diseases do occur in children with leukemia and frequency varies by age, region, and gender. Pediatr Blood Cancer 2013;60:E160–E162. © 2013 Wiley Periodicals, Inc.